Common conceptual flaws in realizing maqāṣid al-Sharīʿah vis-à-vis Islamic finance - Ameen Ahmed Abdullah Qasem Al-Nahari; Abu Talib Mohammad Monawer; Luqman Haji Abdullah; Abdul Karim Ali; Noor Naemah Abdul Rahman; Meguellati Achour (ISRA International Journal of Islamic Finance, 2022)
Purpose - This paper aims to scrutinize the misconceptions about maqāṣid al-Sharīʿah (objectives of Islamic law) that complicate its actualization, particularly in Islamic finance. Design/methodology/approach - This study adopts a qualitative inductive method to identify the flaws in understanding maqāṣid al-Sharīʿah vis-à-vis Islamic finance. It uses the views of classical and modern maqāṣid scholars to critically examine the flaws. Findings - This study concludes that the five objectives of the Sharīʿah constitute the framework of maṣlaḥah (well-being). The levels of maṣlaḥah - namely ḍarūriyyāt (essentials), ḥājiyyāt (needs) and taḥsīniyyāt (embellishments) - are the categories of the means to ends. The demand for financial products falls under the ḥājiyyāt and taḥsīniyyāt categories, not ḍarūriyyāt. The maqāṣid (objectives) are derived from aḥkām (provisions) being verified by the parameters, while aḥkām are guided by maqāṣid. Research limitations/implications - This study recommends further research to theorize the concepts of ḍarūriyyāt, ḥājiyyāt, taḥsīniyyat and mukammilāt (complements); to harmonize the maqāṣid with their essential elements and to formulate a conceptual framework for actualizing maqāṣid al-Sharīʿah in Islamic finance. Practical implications - This paper will improve perceptions and bridge gaps between the understanding of maqāṣid theory and existing practices. It suggests that instead of ḍarūriyyāt, Islamic financial institutions (IFIs) should refer to ḥājiyyāt and taḥsīniyyāt. Originality/value - This paper identifies and clarifies the misconceptions about maqāṣid al-Sharīʿah vis-à-vis Islamic finance in the existing literature. The findings align with the views of leading maqāṣid scholars in understanding the idea.
Keywords: 330; Islamic finance; Maqāṣid al-Sharīʿah; Maṣlaḥah; Parameters; Provisions